Guidelines for Developing Teacher Competency Based on the Coaching Skills Conceptual Framework for School Administrators under the Secondary Educational Service Area Office Bangkok 2 - Singsoong, Nita; Thongkamhaeng, Kamolthip (An Online Journal of Education, 2026)
This research employed a mixed methods research design, comprising two phases. Phase 1, a quantitative study, the essential needs for developing teacher competency based on the coaching skills conceptual framework of school administrators under the secondary educational service area office, Bangkok 2. The sample consisted of 357 teachers from eight schools whitin the educational network, selected through multistage sampling. The research instrument was a 50-item, five-point Likert-scale questionnaire with content validity indices ranging from 0.60 to 1.00, item discrimination values between 0.50 and 0.94, and a reliability coefficient of 0.98. Data were analyzed using descriptive statistics and the modified Priority Needs Index (PNImodified); and Phase 2, a qualitative study, aimed to propose guidelines for teacher competency development. Data were collected through semi-structured interviews with seven purposively selected experts in educational administration. Content analysis was employed for data analysis. The research findings indicated: 1) the highest priority for developing teacher competency was the development of constructive feedback skills (PNImodified = 0.3017), questioning skills (PNImodified = 0.2976), relationship-building skills (PNImodified = 0.2947), active and Intentional listening skills (PNImodified = 0.2922), and motivation and encouragement skills (PNImodified = 0.2849), respectively; and 2) the proposed guidelines for developing teacher competency included communication, empathy, trust, organizational climate, and intrinsic motivation. These results suggest that guidelines for developing teacher competency based on the coaching skills conceptual framework of school administrators should prioritize sincere communication, empathy, and trust. These elements serve as fundamental factors in fostering a safe and support teachers professional practice, while potentially functioning as a strategic approach to enhancing teachers intrinsic motivation.